ANALISIS DETERMINASI DIRI REMAJA - Gina Ayu Nilamsari; Gian Sugiana Sugara; Dewang Sulistiana (Program Studi Bimbingan dan Konseling Universitas Muhammadiyah Tasikmalaya, 2020)
Self-determination is the ability of individuals to direct themselves to achieve life goals that are driven by the fulfillment of autonomous needs, competencies and relationships with others. The purpose of this study was to determine the picture of self-determination in adolescents of class XI SMK As-Saabiq Singaparna, differences based on gender, based on majors and design guidance and counseling services to improve self-determination of adolescent students. This study uses quantitative descriptive methods to uncover the picture of self-determination of adolescent students. The sample in this study was class XI As-Saabiq Singaparna Vocational School, amounting to 191 students, the sample in this study was taken using a saturated sampling technique that is by making the population as a sample sample. The results of this study in general the self-determination of class XI students of SMK As-Saabiq are in the category of high self-determination of 54% (103 students). The highest aspect is competence while the lowest aspect is the autonomy aspect. Based on differences in majors there are differences and based on gender shows Sig. 0.002 which means there is a significant difference between self-determination in male and female students of class XI Vocational School in As-Saabiq. The weaknesses of this study are the sample is still limited so that it only knows the self-determination of class XI students of SMK As-saabiq